Pediatric headache: overview. Issue 6 (December 2018) - Kelly, Meaghan; Strelzik, Jeffrey; Langdon, Raquel; DiSabella, Marc
Abstract : Purpose of review: Headache is a common medical complaint in children and adolescents with the majority having experienced some type of headache by their teenage years. Pediatric headache presentations often differ compared to adults, and children may have difficulty describing their symptoms. Thus, a thorough understanding of the approach to the pediatric headache patient is essential to ensure appropriate diagnosis, evaluation, and management. Recent findings: In the following article we will review the components of a comprehensive pediatric headache assessment, as well as discuss primary and secondary headache types seen in children with focus on clinical pearls and 'red flags' necessitating diagnostic testing. Summary: Headaches in children may be due to primary or secondary etiologies. Common primary headache types include migraine or tension-type headache. Secondary headache causes are broad and include infections, trauma, vascular disorders, substance use/withdrawal, and psychiatric conditions. Current American Academy of Neurology (AAN) guidelines recommend against routine lab studies, lumbar puncture, electro-encephalogram (EEG), or neuroimaging in patients with no headache red flags by history and a normal neurologic examination.